Phenotypic Plasticity of Wild Rice (Oryza nivara) Between the Native and Introduced Environments in Sri Lanka - Wijerathna, P.; Sandamal, S.; Tennakoon, A.; Ratnasekera, D. (University of Jaffna, 2022)
Wild rice species, Oryza nivara is the progenitor of Asian cultivated rice and has been recognized as a valuable genetic resource for rice genetic improvement. In Sri Lanka, reciprocal transplant studies of wild rice species are limited. This study fulfils the knowledge gap on morphological variation of O. nivara grown in native and introduced environments for evaluating phenotypic variation for local adaptation. The reciprocal common garden experiment was conducted in the dry (Hambantota: N6.232684, E81.147097) and wet (Akuressa: N6.162225, E80.42886) zones of Sri Lanka. Phenotypic plasticity was measured by 8 quantitative traits following the rice descriptor published by IRRI. The independent t-test revealed that the all quantitative traits of O. nivara showed a significant difference between the dry and wet zones. According to the results, significantly highest culm length (78.4 ± 11.2 cm), anther length (3.38 ± 0.34 mm), awn length (66.9 ± 14.9 mm), panicle length (24.66 ± 3.25 mm), and plant height (101.2 ± 23.3 cm) were recorded in the wet zone. However, the dry zone showed the significantly highest culm diameter (8.21 ± 1.23 mm), flag leaf angle (850 ), and horizontal distribution (145.0 ± 17.4 cm) compared to the wet zone. Oryza nivara was mostly confined to the dry zone thus, its phenotype was more prominent in the wet zone when compared to its native habitat. The investigation of phenotypic plasticity provides a new clue for the local adaptation and speciation studies and the effective use of wild stains in the development of location-specific modern cultivars.
Keywords: Wild rice; Phenotypic plasticity; Morphological diversity; Local adaptation and speciation; Reciprocal experiment